The last empire of Iran - Jackson Bonner, Michael Richard, 1982- (Piscataway, NJ)
vii, 396 sayfa
Keywords: ''This handbook is a history of the Sasanian dynasty: the rulers of the last Iranian empire before the Arab conquests in the seventh century. Sasanian Iran (220s to AD 651) was the foremost power between Rome and the nomadic world of Iner Asian in Late Antiquity... (4e de couverture)'' --